Management of penile post-circumcision ischemia by pentoxifylline infusion and hyperbaric oxygen therapy - Mohamed A Baky Fahmy; Tarek Abdelazeem Sabra; Sarah Magdy Abdelmohsen (BMC Urology, 2023)
Abstract Background Post-circumcision penile ischemia is a devastating complication. We will present our experience in managing children with various forms of penile ischemia. Materials and methods This cohort prospective observational and interventional study was performed on all male children with post-circumcision penile ischemia between April 2017 and October 2021. A designed and approved protocol includes a combination of early pentoxifylline infusion, hyperbaric oxygen inhalation, early catheterization, and appropriate surgical debridement were applied for patients with deep ischemia 11/23, mainly the necrotic skin and subcutaneous tissues. Data of patient age, anesthesia method, monopolar diathermy usage, early presentation and positive wound culture were collected and analyzed statistically. Results During the study period 3,382 children were circumcised for non-medical reasons; 23 children were diagnosed with penile ischemia (0.7%), among other complications (9%). Most of the penile ischemia is associated with the use of monopolar diathermy (74%). The use of compressive wound dressing to control post-circumcision bleeding and infections is also responsible for ischemia in 52.2% and 43.5% of the cases. Inexperienced physicians were commonly responsible for ischemia (73.9%). Patients managed at first 24 h had better outcomes than those who were presented later (p = 0.001). Conclusion In children with post-circumcision penile ischemia, a combination of hyperbaric oxygen therapy and pentoxifylline is especially effective for patients with skin and facial necrosis, this management reduces penile tissue loss.